Study of Histological and Histochemical Changes of Primary Visual Cerebral Cortex with Aging Process - Rajaa Ali Moheiseen Al-Taee (Journal of Global Pharma Technology, 2018)
Aging has been defined as the sum of all changes produced with the passing of time, lectins are specific carbohydrate-binding proteins; they can be employed as specific probes to localize defined monosaccharide and oligosaccharides on cell surface and on cytoplasmic structures, and in an extracellular matrix. Understanding of ocular changes with aging is based on knowledge of normal ocular structure and histochemistry. For this purpose , this study aimed : to study age-dependent histological and ultrastructural (glycoconjugates) changes in the primary visual cerebral cortex with light and fluorescence microscopy by using routine and five lectin stains to illustrate the patterns of glycoconjugates materials during aging . This study was conducted in the department of biology /college of science, department of anatomy and histology /college of medicine of Babylon University and College of Medicine /Al-Nahrain University, with a total of 40 albino rat .Our finding suggested: an aging appears to alter the carbohydrates components of visual cerebral cortex , The histochemical study during the preceding of age (3 , 8, 24 ,48) weeks revealed variable tempo-spatial variability of lectin bindings to the primary visual cerebral cortex tissue, and referred that different cerebral layers have similar patterns of distribution in some aspect , but dissimilarity in another. In conclusion, The finding of the present study clearly indicate that the lectin bindings could be an indicator for the glycoconjucate changes that play an essential role in aging process by marking cellular differentiation, cellular migration, and cellular interactions.Keywords: Aging, Lectin, Primary Visual Cerebral Cortex, Histology, Histochemistry.